Estructura esquelética craneofacial y su relación con los tejidos blandos. Una revisión narrativa (2021)
To carry out a narrative review of the publication status on the relationship between craniofacial skeletal patterns and the soft tissues of the face. Materials and Methods: Bibliographic search in databases: Pubmed, Science Direct and Google Scholar following an adaptation of the PRISMA protocol for narrative reviews. Review studies, editorial articles, and related documents were excluded.